2020
DOI: 10.1080/00220973.2020.1724851
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Social Environment as Student Emotions' Antecedent: Mediating Role of Achievement Goals

Abstract: In line with assumptions made by the control-value theory of academic emotions, it was hypothesized that the association between the classroom social environment, in terms of students' perceptions of their teachers' interpersonal behaviour, and students' academic emotions was partially mediated by students' achievement goals. The present study applied multilevel structural equation modelling on questionnaire data from a sample of 2000 Chinese secondary school students. As assumed, achievement goals partially m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…Second, we found mastery-approach could negatively predict learning anxiety, which is also consistent with previous studies ( Elliot and McGregor, 1999 ; Shih, 2005 ; Goetz et al, 2016 ; Palazzolo, 2020 ; Sun et al, 2020 ). However, the effect of performance-approach goal orientation on the prediction of learning anxiety was not significant although they were positively correlated, which has been found in some studies ( Smith et al, 2002 ; Mattern, 2005 ; Hong et al, 2018 ; Liu et al, 2020 ) but differed from the results of other studies ( Cooper, 2014 ; Dull et al, 2015 ; Tu and Yang, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Second, we found mastery-approach could negatively predict learning anxiety, which is also consistent with previous studies ( Elliot and McGregor, 1999 ; Shih, 2005 ; Goetz et al, 2016 ; Palazzolo, 2020 ; Sun et al, 2020 ). However, the effect of performance-approach goal orientation on the prediction of learning anxiety was not significant although they were positively correlated, which has been found in some studies ( Smith et al, 2002 ; Mattern, 2005 ; Hong et al, 2018 ; Liu et al, 2020 ) but differed from the results of other studies ( Cooper, 2014 ; Dull et al, 2015 ; Tu and Yang, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the third category is negative emotions that lack subjective control. Finally, the fourth type of emotion is characterized by a relatively high level of control [ 21 , 22 ]. The specific performance of the four dimensions of academic emotion is depicted in Figure 2 .…”
Section: An Overview Of the Relevant Theories And The Flow Of Researc...mentioning
confidence: 99%
“…Unpleasant emotions, such as anxiety, occur when students perceive teachers as cold or distant, such as punishing (Frenzel et al, 2007) or enforcing achievement (Goetz et al, 2006). Mainhard et al (2018) found that student perceptions of teacher closeness accounted for substantial variance in student enjoyment and anxiety and findings by Sun et al (2022) and Donker et al (2021) generally corroborated these results. In line with this, Goetz et al (2021) found in a longitudinal study that teacher closeness was associated with students' positive emotional experiences (and negatively with unpleasant emotions).…”
Section: Introductionmentioning
confidence: 80%